2019
DOI: 10.1097/ccm.0000000000003967
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated Hexa-Acyl Disaccharides Augment Host Resistance Against Common Nosocomial Pathogens

Abstract: Objectives: To determine whether synthetic phosphorylated hexa-acyl disaccharides provide antimicrobial protection in clinically relevant models of bacterial infection. Design: Laboratory study. Setting: University laboratory. Subjects: BALB/c, C57BL/10J, and C57BL/10ScNJ mice. Interventions: Mice were treated with la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…PHADs similarly bind TLR4 and activate both MyD88- and TRIF-dependent signaling. Hernandez and colleagues recently showed that treating mice with PHADs confers protection to P. aeruginosa and S. aureus , both of which are of high clinical relevance ( 77 ). They found the survival benefit to be associated with increased bacterial clearance, an effect which was observed up to 10 days after treatment.…”
Section: Toll-like Receptor Agonist-mediated Trained Immunity and Promentioning
confidence: 99%
See 1 more Smart Citation
“…PHADs similarly bind TLR4 and activate both MyD88- and TRIF-dependent signaling. Hernandez and colleagues recently showed that treating mice with PHADs confers protection to P. aeruginosa and S. aureus , both of which are of high clinical relevance ( 77 ). They found the survival benefit to be associated with increased bacterial clearance, an effect which was observed up to 10 days after treatment.…”
Section: Toll-like Receptor Agonist-mediated Trained Immunity and Promentioning
confidence: 99%
“…They found the survival benefit to be associated with increased bacterial clearance, an effect which was observed up to 10 days after treatment. Further, treatment with PHADs increased leukocyte recruitment and antimicrobial functions while attenuating systemic and local levels of proinflammatory cytokines ( 77 ).…”
Section: Toll-like Receptor Agonist-mediated Trained Immunity and Promentioning
confidence: 99%
“…Trained immunity refers to a long-term functional reprogramming of innate leukocytes, evoked by a prior exposure to microbial ligands or a non-lethal infectious insult, which leads to an amplified anti-microbial response to a broad range of secondary infections (147). Trained immunity induced by microbial ligands such as Toll-like receptor 4 agonists (TLR4), including Monophosphoryl lipid-A (MPLA) and fungal ligand b-glucan, potently protects against life-threatening pathogens such as Pseudomonas aeruginosa, Staphylococcus aureus, and Mycobacterium tuberculosis (148)(149)(150)(151). TLR4 agonist-induced trained immunity involves metabolic reprogramming of macrophages including mitochondrial biogenesis and augmentation of glycolysis and mitochondrial oxidative phosphorylation (149,152).…”
Section: Can Therapeutics Targeting Immune Checkpoints Augment Trained Immunity-mediated Protection Against Infections?mentioning
confidence: 99%
“…Investigation of trained immunity has been an active field of research with major discoveries advancing the field towards therapeutic translation for several applications; however, much remains to be explored before the true immunomodulatory potential of training agents can come to fruition. Toll-like receptor (TLR)-4 agonists have been shown to trigger host resistance to infection that lasts for up to two weeks in several clinically relevant models of infection ( 10, 11, 15 ), which our group has revealed to be driven by long-term changes in innate immune function supported by metabolic rewiring ( 13 ). We sought to define which signaling pathway(s) mediate immune training given that TLR4 uniquely signals through both MyD88- and TRIF-dependent signaling cascades.…”
Section: Discussionmentioning
confidence: 99%